QUALITY AND PROCESS IMPROVEMENT IN ONLINE DISTANCE EDUCATION SERVICES (Third Sector Social Economic Review, 2024)
Sustainable Development Goal 4 aims to provide inclusive and quality education for all individuals, but its progression was disrupted during the pandemic. The COVID-19 pandemic, a traumatic event just like wars and the great depression worldwide, has affected all areas like consumers, supply chains, and education. COVID-19 and quarantines made college students more vulnerable than adults as their universities were physically closed, and they were unemployed. The current study presents operations and consumer perspectives on online education services. Therefore, this study aims to provide a map for quality and process improvement in online distance education by examining the experiences of university students during the COVID-19 pandemic. In this context, in-depth interviews were conducted with thirty-nine university students in the emerging market, Turkey. The analysis of the qualitative data was carried out using the thematic analysis approach. This study benefits from behavioral reasoning theory and lean methodology. We found reasons against online distance education adoption include universities’ unreadiness, inequality in accessing sufficient technology and electricity, students’ unreadiness, and stressors. On the other hand, the reasons for adopting online distance education are perceived benefits. In conclusion, suggestions for implications and future research are given.
Keywords: online distance education; quality improvement; lean methodology; process improvement; sustainable development goals.